Influence of the use of food with addition of mineral adsorbents on economic results in chicken fattening - Tica, Nedeljko; Okanović, Đ.; Zekić, V.; Karović, D.; Milić, D. (Economics of Agriculture, 2010)
The aim of the research is to identify whether the mineral adsorbents added to the food of fattening chicken have impact on the cost-effectiveness of the fattening. The research was conducted on 400 fattening chicken, Cobb 500 provenience, divided into 4 groups, depending on the level of added mineral adsorbent: control group K (100 chicken, no mineral adsorbent added, 0,0%); experimental group O-I (100 chicken, with 0,5% of mineral adsorbents), experimental group O-II (100 chicken, with 0,2% of Processed mineral adsorbents) and experimental group O-III (100 chicken, with 0,3% of processed mineral adsorbents). Diet experiment lasted for 42 days. Results of the research show that chicken from O-I group had the best production results, followed by O-III, O-II and K as the poorest group. Calculations conducted during the work, it has been established that the addition of mineral adsorbents into the fattening chicken diet had very good effects on production and economic results.